The Strategies Used by Animal Viruses to Antagonize Host Antiviral Innate Immunity: New Clues for Developing Live Attenuated Vaccines (LAVs) - Na Chen; Baoge Zhang (Vaccines)
As an essential type of vaccine, live attenuated vaccines (LAVs) play a crucial role in animal disease prevention and control. Nevertheless, developing LAVs faces the challenge of balancing safety and efficacy. Understanding the mechanisms animal viruses use to antagonize host antiviral innate immunity may help to precisely regulate vaccine strains and maintain strong immunogenicity while reducing their pathogenicity. It may improve the safety and efficacy of LAVs, as well as provide a more reliable means for the prevention and control of infectious livestock diseases. Therefore, exploring viral antagonistic mechanisms is a significant clue for developing LAVs, which helps to explore more viral virulence factors (as new vaccine targets) and provides a vital theoretical basis and technical support for vaccine development. Among animal viruses, ASFV, PRRSV, PRV, CSFV, FMDV, PCV, PPV, and AIV are some typical representatives. It is crucial to conduct in-depth research and summarize the antagonistic strategies of these typical animal viruses. Studies have indicated that animal viruses may antagonize the antiviral innate immunity by directly or indirectly blocking the antiviral signaling pathways. In addition, viruses also do this by antagonizing host restriction factors targeting the viral replication cycle. Beyond that, viruses may antagonize via regulating apoptosis, metabolic pathways, and stress granule formation. A summary of viral antagonistic mechanisms might provide a new theoretical basis for understanding the pathogenic mechanism of animal viruses and developing LAVs based on antagonistic mechanisms and viral virulence factors.